Evaluation of the Adolescent Posyandu in the Working Area of Puskesmas Wonokerto I, Pekalongan Regency - Febriyanti, Rinda Febriyanti; Priharwanti, Ardiana; Wahyuningsih; Yuniarti (Universitas Nahdlatul Ulama Surabaya, 2025)
The Adolescent Posyandu is a form of mentoring and coaching designed to help teenagers avoid negative behaviors that may harm themselves or others. In the current digital era, where information can be easily accessed through the internet and social media, the implementation of Adolescent Posyandu faces various challenges. This study aimed to evaluate the implementation of the Adolescent Posyandu in the working area of Puskesmas Wonokerto I, Pekalongan Regency. This descriptive qualitative research used in-depth interviews in which the data were analyzed using the Context–Input–Process–Product (CIPP) model. At the context stage, the program had not been fully achieved due to low participant coverage, uneven target distribution, and environmental factors such as peer influence and cadre roles that affected participation. At the input stage, not all cadres had attended training, and the number of cadres did not meet the technical guidelines. At the process stage, scheduling was constrained by the busy schedules of officers, and activities were incomplete. Monitoring and evaluation by the health center were also limited. At the product stage, there were no innovative activities to increase adolescents’ awareness and participation. Puskesmas Wonokerto I needs to optimize the development of Adolescent Posyandu activities by improving human resources, facilities, monitoring, and innovative approaches.